Effect of nonylphenol on volatile fatty acids accumulation during anaerobic fermentation of waste activated sludge. (15th November 2016) - Duan, Xu; Wang, Xiao; Xie, Jing; Feng, Leiyu; Yan, Yuanyuan; Zhou, Qi
Abstract: Most of the reported studies on anaerobic fermentation of sludge focused on the influences of operating conditions, pretreatment methods, and its characteristics, and little attention was paid to those of persistent organic pollutants (POPs) which widespreadly appeared in sludge. In this study, the effect of nonylphenol, a typical POPs in waste activated sludge (WAS), on anaerobic fermentation for volatile fatty acids (VFAs) accumulation was investigated. The concentration of VFAs during WAS anaerobic fermentation was found to be affected positively from 2856 mg COD/L in the control (without NP) to 5620 mg COD/L with NP of 200 mg/kg dry sludge. Mechanism exploration exhibited that the main reason for the enhanced VFAs accumulation in the presence of NP was that more acetic acid was generated during the acidification of WAS, which was increased by almost three times (3790 versus 1310 mg COD/L). In WAS fermentation systems, the abundance of anaerobic functional microorganisms was advantageous to the accumulation of acetic acid. Further investigation by the pure acetogen revealed that both the viability and activity of Proteiniphilum acetatigenes were improved by NP during anaerobic fermentation, resulting in more production of acetic acid and showing good agreement with that in the real WAS fermentation systems. Graphical abstract: Highlights: WAS anaerobic fermentation was positively influenced by nonylphenol. The production of VFAs, especially acetic acid was enhanced by nonylphenol. NP stimulated WAS acidification but affected solubilization and hydrolysis little. The microorganism abundance was advantageous to the accumulation of acetic acid. The viability and activity of acetogen were improved in the presence of NP.